Conflicting Priorities in Social Legislation and Medicine: Gynaeco-oncology Patients and their Right to Participate in Society - Simoes, E.; Graf, J.; Wallwiener, D.; Brucker, S. (Geburtshilfe und Frauenheilkunde, 2015)
Due to the declining mortality rates, malignant diseases have gained a chronic character for many gynaeco-oncology patients. The patients can expect to participate in social life and to an increasing extent in professional life for longer lengths of time. Promotion of rehabilitation and participation is an issue of the German 9th Social Security Code that explicitly places a focus on women. This is mainly of relevance for tumour patients with regard to assessment of the degree of severe disability, to compensate for disease-induced impairments and the possibilities for improving the participation of the afflicted subjects, especially by means of protective rights in professional life. Indeed, tumour patients do sometimes find themselves confronted with conflicting priorities between the entitlements guaranteed by social legislation and the compensation conferred by the health-care services, which can then be avoided when the facts are sufficiently known. For this purpose, the physician must be fully aware of the legal situation. The present article provides an overview of the procedures and reference points for appraisals. Patients need partners among their responsible physicians to help in the assertion of their claims. From the physicianʼs side it is necessary to classify the reported complaints within the ever increasing knowledge about the direct side effects and the long-term side effects of cancer therapies. Against the background of an often life-long mental stress and the uncertain risk of recurrence, it should also be considered whether the concept of healing probation is in support of the targets of long-term disease management and social reintegration, also in the interest of society in general.
Keywords: participation; severe disability; gynaeco-oncology; social legislation